[Dance Company (NSW) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Further related material is located in other PROMPT collections under Graeme Murphy and the Sydney Dance Company.
The Dance Company (NSW) was originally founded in 1969 as the dance-in-education group Ballet in a Nutshell by by Suzanne Musitz (Davidson). The group later changed its name to Athletes and Dancers, and Dance Company (NSW) in 1976. In 1979 the company was renamed the Sydney Dance Company by its new artistic director Graeme Murphy, who had joined the Dance Company (NSW) in 1976. Sydney Dance Company is one of Australia's most successful and well-known contemporary dance companies.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Murphy, Graeme, -- 1950- -- Miscellanea; Dance Company (NSW) -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian